(untitled) (Olhar de Professor, 2012)
This article is based on fi eldwork carried out during research conducted in a public school in Lisbon. Cinema is used as a medium for refl ection on violence, citizenship and youth. First of all, the article tries to understand through some fi lms the movement that happens when fictional cinema attempts, through the theme of the reality of poor, excluded children and young people, to bring the lives of these young people to the screen and secondly, the view that young people have of these fi lms and how to use cinema as a medium by which they might feel stimulated to externalize what they think, feel and see. In order to see through the eyes of young people an ethnographic research was developed for six months and used as the "fi eld of study" a secondary school situated within the urban area of Lisbon. The aim of this research was to understand how young people see themselves and how they think they are seen by society (which includes the cinema, the media, etc.) of which they are a part. The author used a research notebook diary depicting daily life at the school as a research tool. The philosophy of this field work is based on the dialectical pedagogy of Paulo Freire. Using problematizing dialogue, mainly developed after the showing of films and during classes and meetings, questioning and problematization was encouraged; and through questions opinions and ideas a video was produced. Utilizing education ’for’, ’with’ and ’about’ the media concepts of communication, education and participation were used, working with issues related to the daily lives of these young people. The fi nal product of this project was a documentary, in which the students were involved in all stages of execution, from pre-production to completion.